Pengaruh Pemberian Aromaterapi Lemon Terhadap Cemas Pada Ibu Nifas Sebagai Upaya Antisipasi Postpartum Blues di RSUD dr. Doris Sylvanus Palangka Raya - Putri, Pira; Mawaddah, Sofia; Noordiati, Noordiati (Midwifery Departement Poltekkes Kemenkes Banjarmasin, 2024)
The results of Basic Health Research in 2018 stated that the prevalence of mental disorders such as depression and anxiety disorders in postpartum mothers was 19.8% of the ± 14 million Indonesian population and in 2022 the incidence of postpartum blues in Asia was quite high, between 26-85%, while In Indonesia, the incidence of postpartum blues is in the range of 50-70%. Unresolved anxiety in postpartum mothers can cause postpartum blues and other health problems. This level of anxiety can be overcome, one of the ways, is through non-pharmacological therapy or natural methods, namely by complementary therapy using aromatherapy.This study aims to determine the effect of giving lemon aromatherapy on anxiety in postpartum mothers as an effort to anticipate postpartum blues at Dr. Doris Sylvanus Hospital, Palangka Raya.This research used a pre-experimental design method on 53 postpartum mother respondents as research samples, who were taken using a purposive sampling technique at RSUD dr. Doris Sylvanus Palangka Raya. Data collection used a questionnaire, data analysis used the T-test.The results of this research show p-value = 0.000 (p < 0.05), which means that there is an influence of lemon aromatherapy on the level of anxiety in postpartum mothers in anticipating postpartum blues at Dr. Doris Sylvanus Hospital, Palangka Raya.Keywords: Lemon aromatherapy, anxiety level, postpartum mothers